(18-3x)-(4+2x)=10

Simple and best practice solution for (18-3x)-(4+2x)=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (18-3x)-(4+2x)=10 equation:


Simplifying
(18 + -3x) + -1(4 + 2x) = 10

Remove parenthesis around (18 + -3x)
18 + -3x + -1(4 + 2x) = 10
18 + -3x + (4 * -1 + 2x * -1) = 10
18 + -3x + (-4 + -2x) = 10

Reorder the terms:
18 + -4 + -3x + -2x = 10

Combine like terms: 18 + -4 = 14
14 + -3x + -2x = 10

Combine like terms: -3x + -2x = -5x
14 + -5x = 10

Solving
14 + -5x = 10

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-14' to each side of the equation.
14 + -14 + -5x = 10 + -14

Combine like terms: 14 + -14 = 0
0 + -5x = 10 + -14
-5x = 10 + -14

Combine like terms: 10 + -14 = -4
-5x = -4

Divide each side by '-5'.
x = 0.8

Simplifying
x = 0.8

See similar equations:

| -4-2(3-x)=-2(x+3) | | -16=6+4+3x | | -6x^3+9x^2-3=0 | | 3=y-n+h | | -8=13-7x | | xy=1+3x | | N=y-n+h | | 6x^3-9x^2+3=0 | | yx=1+3x | | x+4.7=-6.2 | | yx=1+3y | | 8x-4=-2x | | 4x^2+4x+21=0 | | (2x-2)+(x+11)=180 | | -7(x+9)=9(k-5)-14k | | -4.9x^2+21x-55=0 | | 4(13-3x)-17=-5x | | c(x)=0.14x | | 49v^3-4v=0 | | 12y+6=6(2y+10) | | 1.2x-0.5=0.1 | | 8x^2-30x-25=0 | | -4.9x^2+21x=55 | | 80=x+(x-10) | | 12-(n-6)+4n-2=n+14 | | x+6.5=-7.6 | | 4+xi=y-7i | | -3(7x+7)-5(x-7)=14 | | X+25+3x=-9+-3x+-15 | | 6g^3-2g^2+4g=0 | | 6x^2-5x-7=-8 | | 7x-127=0 |

Equations solver categories